2001
DOI: 10.2134/jeq2001.1911
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Phenanthrene Biodegradation in Soil by Slender Oat Root Exudates and Root Debris

Abstract: To investigate the mechanisms by which slender oat (Avena barbata Pott ex Link) enhances phenanthrene biodegradation, we analyzed the impacts of root exudates and root debris on phenanthrene biodegradation and degrader community dynamics. Accelerated phenanthrene biodegradation rates occurred in soils amended with slender oat root exudates as well as combined root debris + root exudate as compared with unamended controls. Root exudates significantly enhanced phenanthrene biodegradation in rhizosphere soils, ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
79
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(86 citation statements)
references
References 34 publications
6
79
0
1
Order By: Relevance
“…One of the most interesting features of phytoremediation is that many plant-derived chemicals (root degradation compounds, secondary metabolites, etc.) stimulate microorganisms to degrade contaminants (Donnelly et al, 1994;Fletcher and Hegde, 1995;Haby and Crowley, 1996;Miya and Firestone, 2001;Isidorov and Jdanova, 2002). Many of these plant-derived compounds are PAH analogs (Singer et al, 2003), and the rhizosphere of plants growing in uncontaminated soils is already enriched in PAH-degrading microorganisms (Daane et al, 2001).…”
Section: Increased Expression Of Hydrocarbon Degradation Genesmentioning
confidence: 99%
“…One of the most interesting features of phytoremediation is that many plant-derived chemicals (root degradation compounds, secondary metabolites, etc.) stimulate microorganisms to degrade contaminants (Donnelly et al, 1994;Fletcher and Hegde, 1995;Haby and Crowley, 1996;Miya and Firestone, 2001;Isidorov and Jdanova, 2002). Many of these plant-derived compounds are PAH analogs (Singer et al, 2003), and the rhizosphere of plants growing in uncontaminated soils is already enriched in PAH-degrading microorganisms (Daane et al, 2001).…”
Section: Increased Expression Of Hydrocarbon Degradation Genesmentioning
confidence: 99%
“…Root exudates are likely to stimulate soil microbial diversity and activity and thereby facilitate microbial biodegradation of organic contaminants. Both in vivo and in vitro experiments have demonstrated that root exudates can enhance microbial biodegradation of petroleum hydrocarbons in soils (Miya and Firestone 2001;Joner et al 2002;Corgié et al 2004Corgié et al , 2006. Research by Yoshitomi and Shann (2001) has shown that root exudates stimulate microbial mineralization of polycyclic aromatic hydrocarbons (PAHs) by the growth of soil microorganisms and the changes in structure and function of microbial community.…”
Section: Introductionmentioning
confidence: 99%
“…Root exudation is now considered to be the most important factor in the mediation of hydrocarbon biodegradation in the rhizosphere [54, 67,104,141,[227][228][229][230][231][232]. Root exudates serve as a carbon source and energy for microorganisms, and also improve the hydrocarbon degradation in the rhizosphere by stimulating hydrocarbon-degrader populations [67].…”
Section: Impact Of Root Exudates On Hydrocarbon Degradationmentioning
confidence: 99%
“…Increasing the microbial biomass and activity by exudation of labile C and N can be a solution. For example, the addition of root debris to phenanthrene contaminated soils only improve phenanthrene degradation after 20 days, in contrast to more labile water soluble exudates, which reflects the low biodegradability of the root debris [231]. In contrast, the high solubility of low molecular weight exudates allows them a higher mobility in soil and a rapid uptake by microbial cells [54].…”
Section: Impact Of Root Exudates On Hydrocarbon Degradationmentioning
confidence: 99%